2018
DOI: 10.1097/iae.0000000000001875
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Inner-Retinal Changes and Outer-Retinal Damage in Patients With Idiopathic Epiretinal Membrane

Abstract: The inner-retinal irregularity index differed significantly according to the IZ status and also correlated with the IZ defect before and after ERM surgery. The inner-retinal irregularity index may reflect the outer-retinal damage in ERM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 29 publications
0
16
0
15
Order By: Relevance
“…16 Some studies have analyzed the predictive values of outer retinal integrity, such as foveal photoreceptors for the prognostic factor of postoperative visual outcome in ERMs, 17,18 and other studies have reported that the inner retinal irregularity index was significantly correlated with visual outcomes before and after ERM surgery. This inner retinal irregularity was found to correlate with outer retinal changes before and after ERM surgery, 19,20 suggesting an important role for inner retinal changes in visual recovery after pars plana vitrectomy with ERM peeling. Distortion of the inner retina was caused by the tractional membrane of the ERM, and as a result permanent functional impairment of the fovea decreased visual acuity after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…16 Some studies have analyzed the predictive values of outer retinal integrity, such as foveal photoreceptors for the prognostic factor of postoperative visual outcome in ERMs, 17,18 and other studies have reported that the inner retinal irregularity index was significantly correlated with visual outcomes before and after ERM surgery. This inner retinal irregularity was found to correlate with outer retinal changes before and after ERM surgery, 19,20 suggesting an important role for inner retinal changes in visual recovery after pars plana vitrectomy with ERM peeling. Distortion of the inner retina was caused by the tractional membrane of the ERM, and as a result permanent functional impairment of the fovea decreased visual acuity after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…В литературе показана зависимость ОЗ после удаления идиопатических ЭММ от длительности заболевания [10,11], предоперационной степени деформации внутренних слоев сетчатки [13,14], наличия КМО [9], толщины центральной сетчатки [13,15], состояния наружных слоев сетчатки [12] 68 тракционному смещению (или эктопии) внутреннего ядерного и внутреннего плексиформного слоев. Это сопровождается увеличением толщины внутренних слоев и центра макулы в целом.…”
Section: Discussionunclassified
“…K. Cho и соавт. [13] продемонстрировали зависимость ОЗ после удаления ЭММ от величины ИИВС В -отношения длины границы между внутренним плексиформным и внутренним ядерным слоями к длине ПЭС. В норме описанная граница регулярна [12,19], а ее длина лишь минимально превышает длину ПЭС.…”
Section: Discussionunclassified
See 2 more Smart Citations